COMPETITIVE STRATEGY AS INSTRUMENT OF INCREASE OF BUSINESS ACTIVITY OF THE INDUSTRIAL ENTERPRISE - Sergeyevich Levchenko, Alexander; Andriyovych Rudychev, Anatoly; Anatolyevna Kuznetsova, Irina; Aleksandrovna Nikitina, Elena (Journal of Applied Engineering Science, 2015)
The achievement of stable economic development of an economic entity and growth of its competitiveness make it necessary to increase the level of its business activity on the basis of improvement of strategic management process. The mechanism of development of the competitive strategy of an economic entity providing transparency and predictability of its activity has been given in this article. Practical realization of the developed strategy is possible, first of all, due to determining of the priority directions of development of an enterprise on the basis of activization of key subsystems of business activity. It is caused, first of all, by the fact that it is almost impossible to provide simultaneous growth of all components of business activity of an enterprise, despite their close interrelation.